Novel binder-free carbon anode for high capacity Li-ion batteries. (May 2021) - Yarmolich, Dmitry; Odarchenko, Yaroslav; Murphy, Carmen; Petrucco, Enrico A.; Cookson, James; Yarmolich, Dzianis; Zhao, Teng; Kim, Hyun-Kyung; Kumar, R. Vasant; Tomov, Rumen I.
Abstract: Novel binder-free, high capacity carbon-based anodes were manufactured using Virtual Cathode Deposition technique in an industrially scalable process. The deposition process transformed a commercial graphite target material into a novel carbon polymorph coating, which was used as Li-ion battery anode. Such anodes displayed first cycle specific capacity of ~1250 mAh g -1 and retained a capacity of more than 900 mAh g -1 at 0.1 C rate and more than 600 mAh g -1 at 0.5 A g -1 rate during cycling. Coulombic efficiencies above 99.5% were attained for 500 cycles. The anodes showed excellent volumetric (>1400 Ah L -1 ) and areal capacity (~4.5 mAh cm - 2 ). Detailed structural characterisation revealed controllably induced packing polymorphism and high surface area (~2100 m 2 g -1 ). The hierarchical architecture of the coatings was composed predominantly of meso- and macro-pores observed in a disordered carbon matrix encompassing nano-sized sp 2 -clusters (average size ~ 15–20 nm) cross-linked by a network of sp 3 -bonded atomic sites. A growth model based on the subsurface implantation mechanism was adopted to explain the formation of this unique structure responsible for the measured high specific capacity and good Coulombic efficiency. Graphical Abstract: ga1 Highlights: Novel Carbon electrode for high capacity Li-ion batteries with process induced polymorphism Binder free anodes for high volumetric density Virtual Cathode Deposition as scalable production method Stable cycling performance with high Coulombic efficiency